Digital Transformation Strategies for Effective Business Management in SMEs: A SmartPLS Approach - Ekawaty, Anita; Rizky, Agung; Ramadan, Ahmad; Ndlovu, Zinhle (APTISI Transactions on Management (ATM), 2025)
Small and Medium Enterprises (SMEs) in Tangerang, Indonesia, significantly contribute to economic development but face barriers in adopting digital technologies, such as limited resources, lack of digital skills, and organizational resistance. Digital transformation, encompassing cloud computing, digital marketing, automation, and data analytics, is increasingly recognized as essential for business growth and efficiency.  The primary objective of this study is to examine the impact of digital transformation strategies on operational efficiency, customer engagement, and overall performance in SMEs. Using a quantitative research approach, Partial Least Squares Structural Equation Modeling (SmartPLS) was applied to analyze data from 150 SMEs in Tangerang. The research measured the relationship between digital transformation strategies and key performance indicators. The results indicate that cloud computing and data analytics significantly improve operational efficiency by streamlining processes and enabling data-driven decision-making. Meanwhile, digital marketing and automation enhance customer engagement and market competitiveness, with SMEs showing stronger customer relationships and improved market positions. This study highlights the importance of adopting digital transformation to enhance SME business management and achieve sustainable growth. It offers practical insights for managers and policymakers and encourages future research on the long-term effects of digital transformation on SME resilience and innovation.